Piper barberi gamble - a redescription of the species with a note on the karyotype - JOHNSON K GEORGE, P N RAVINDRAN, K NIRMAL BABU, R RAMAKRISHNAN NAIR, (Journal of Spices and Aromatic Crops, 1992)
P. barberi was described by Gamble (1924) based on the male plants only. Here the species is being redescribed based on the female plant characters as well. P. barberi is a unique species among the Piper taxa occurring in South India. The somatic chromosome numbel’ of P. barberi was determined to be 2n = 52.